Social Media's Democratic Footprint: A Review of Political Participation Trends - Nusantara, Garda; Kinkin Yuliaty Subarsa (LSPR Institute of Communication & Business, 2025)
This literature review examines social media's role in increasing public political engagement in the digital era, synthesizing 17 scientific sources from the last five years. Digital transformation has reshaped political participation, fostering faster, more open, and decentralized interactions. The study explores five key themes: the theoretical basis of political participation, mechanisms for increasing engagement through social media (e.g., shaping public opinion via digital platforms and phenomena like